UNDERGRADUATES’ PERCEPTION OF UNETHICAL PRACTICES AMONG LECTURERS IN HIGHER INSTITUTIONS IN DELTA STATE - C. C., Abanobi, (IJRDO- Journal of Educational Research, 2017)
The issue of unethical practices is now the bane of some higher institutions in Nigeria. This studytherefore ascertained undergraduates’ perceptions on unethical practices among lecturers inhigher institutions in Delta State. Three research questions were raised and answered. Twohypotheses were formulated and tested. The study used a descriptive survey design. The studentsof Federal College of Education (Technical), Asaba, and Delta State University Abraka,comprised the population of the study. 247 students (112 males and 135 females) were selectedacross the institutions using convenience sampling technique. The instrument used for datacollection was a questionnaire entitled ‘Undergraduates’ Perception of Unethical PracticesQuestionnaire (UPUPQ)’. The face and content validity of UPUPQ was established by twoexperts in Measurement and Evaluation. The reliability coefficient of the instrument usingCronbach Alpha method was 0.76. The data collected were analyzed using mean statistics toaddress the research questions while the hypotheses were tested at .05 level of significance usingt-test analysis. The findings revealed that some lecturers in higher institutions engage inunethical practices. Furthermore, factors such as that desperation for promotion, greed formoney and many others are causes of unethical practices among lecturers in higher institutions.Also, the difference in the mean perception scores of male and female students on unethicalpractices among lecturers in higher institutions is not significant. Finally, the difference in themean perception scores of male and female undergraduates on perceived causes of unethicalpractices among lecturers in higher institutions is not significant. Based on the findings, thestudy recommended among others that various higher institutions authority should organizeseminar on ethical re-orientation for academic staff in order to combat unethical practices inschools.